2017
DOI: 10.14341/dm7920
|View full text |Cite
|
Sign up to set email alerts
|

MODY in Siberia – molecular genetics and clinical characteristics

Abstract: Institution of Internal and Preventive Medicine, Novosibirsk, Russia The diagnosis of maturity onset diabetes of the young (MODY) has high clinical significance in young patients (no absolute need for exogenous insulin; normoglycaemia in most patients achieved by dieting or taking oral hypoglycaemic agents) and their relatives (high probability of first-degree relatives being carriers of mutations, which requires a thorough collection of family history and determination of the parameters of carbohydrate metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, when examining Iranian families with diabetes, Sarmadi et al ( 20 ) concluded that the CEL variant p.Ile488Thr causes MODY, even if present at an allele frequency of 0.01 in various Middle Eastern populations. Other single cases or families proposed to carry pathogenic CEL mutations outside the VNTR have been published from India ( 21 ), Siberia ( 22 ), China ( 23 ), and South Korea ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when examining Iranian families with diabetes, Sarmadi et al ( 20 ) concluded that the CEL variant p.Ile488Thr causes MODY, even if present at an allele frequency of 0.01 in various Middle Eastern populations. Other single cases or families proposed to carry pathogenic CEL mutations outside the VNTR have been published from India ( 21 ), Siberia ( 22 ), China ( 23 ), and South Korea ( 24 ).…”
Section: Discussionmentioning
confidence: 99%